2021
DOI: 10.1115/1.4052134
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Influence of a Bleed on the Last Stage of a Low-Pressure Compressor and S-Duct

Abstract: This paper uses Computational Fluid Dynamics to investigate the effect of an engine handling bleed situated on the outer casing downstream of the last rotor stage of a low-pressure compressor and upstream of the outlet guide vane and S-shaped duct. The model, validated against existing experimental data, utilized an unsteady RANS solver incorporating a Reynolds stress closure to examine the unsteady component interactions. The results showed that at bleed rates less than 25% of the mainstream flow the bleed ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Building upon the aforementioned studies on bleed effects, numerous investigations [17][18][19][20][21][22][23] have demonstrated that effective control of compressor leakage flow through a well-designed bleed arrangement is crucial for enhancing compressor performance. Therefore, it is of great value to analyze overall performance parameters of the rotor, the distribution of key aerodynamic parameters, and structural changes in the flow field at the blade tip.…”
Section: Introductionmentioning
confidence: 99%
“…Building upon the aforementioned studies on bleed effects, numerous investigations [17][18][19][20][21][22][23] have demonstrated that effective control of compressor leakage flow through a well-designed bleed arrangement is crucial for enhancing compressor performance. Therefore, it is of great value to analyze overall performance parameters of the rotor, the distribution of key aerodynamic parameters, and structural changes in the flow field at the blade tip.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the bypass duct of a gas turbine, the preferred option is flush or submerged off-takes as they can minimise the aerodynamic effect on the bypass stream and the associated impact in efficiency and SFC. Examples of work em ploying flush off-takes in the bypass duct can be found at Walker et al [1,5] and Spanelis and Walker [6].…”
Section: Introductionmentioning
confidence: 99%
“…See for example A'Barrow et al [11] who illustrates that the presence of a diffusing off-take downstream of a compressor can have an upstream effect on the compressor and similarly the compressor's exit conditions will also affect the performance of the diffusing off-take. Additionally, Spanelis and Walker [6] who investigated the effects of an annular bleed between the stator and the rotor of a low-pressure compressor, showed that the position of the bleed is responsible for severe flow bias in the radial direction which can reduce the OGV stall margin and alter the OGV stall topology itself. The current system can be described by a large set of closely coupled design variables which define the aerodynamic shape.…”
Section: Introductionmentioning
confidence: 99%